Induksi dan Regenerasi Embriogenesis Somatik Pepaya - Sutanto, Agus; Aziz, M A (Jurnal Hortikultura, 2006)
Penelitian ini bertujuan menginduksi dan meregenerasi embrio somatik dari embrio zigotik buah pepaya muda kultivar Eksotika II. Kegiatan dilaksanakan di laboratorium Kultur Jaringan Jabatan Sains Tanaman, Universiti Putra Malaysia pada bulan Januari sampai Agustus 2001. Penelitian ini menggunakan rancangan acak lengkap dengan perlakuan kombinasi beberapa konsentrasi 2,4-D (1,0; 2,5 dan 5,0 mg/l) dan BAP (0; 0,001; 0,005; dan 0,01 mg/l). Hasil penelitian menunjukkan bahwa media MS yang mengandung 5,0 mg/l 2,4-D membentuk embrio somatik tertinggi (74,55%) dan kombinasi dari 2,4-D 1,0 mg/l dan BAP 0,01 mg/l menghasilkan kalus tertinggi (52,58%) pada 8 minggu setelah kultur. Jumlah embrio somatik per eksplan terbanyak (66,61) diperoleh pada media MS dengan 5,0 mg/l 2,4-D dan 0,01 mg/l BAP. Pemasakan embrio diperoleh dengan memindahkan embrio globular ke media padat MS tanpa zat pengatur tumbuh. Empat minggu setelah kultur, 42% embrio somatik berkecambah setelah embrio masak. Plantlet siap diaklimatisasi pada 8 minggu setelah kultur ke media perkecambahan. Sistem perbanyakan dan regenerasi embrio somatik pepaya ini dapat menunjang keberhasilan pemuliaan tanaman pepaya modern melalui transformasi genetikThe experiments with the objectives to induce and regenerate somatic embryogenesis were carried out at the Tissue Culture Laboratory of Crop Science Department, Universiti Putra Malaysia from January to August 2001. The experiments involved the induction of somatic embryogenesis from immature zygotic embryos of papaya cv. Eksotika II and regeneration of plantlets from the somatic embryos. A nonfactorial completely randomized design was used as experimental design with treatments of the 2.4-D combinations concentrations (1.0; 2.5 and 5.0 mg/l) and BAP concentrations (0; 0.001; 0.005 and 0.01 mg/l). The results showed that MS medium supplemented with 2,4-D 5.0 mg/l promoted the highest percentage of somatic embryogenesis (74.55%), while the combination of 1.0 mg/l 2,4-D and 0.01 mg/l BAP produced the highest percentage of callus formation (52.58%) after 8 weeks of culture. The highest number of somatic embryos per explant (66.61) was obtained when 5.0 mg/l 2,4-D and 0.01 mg/l BAP were added into MS medium. Maturation of somatic embryos was achieved on transfering the globular somatic embryos derived from zigotic embryo to solid MS medium without growth regulator. After 4 weeks of culture, 42% germinated somatic embryo was occurred following maturation of somatic embryos. Plantlets were ready for acclimatization to germination medium 8 weeks after culture. Somatic embryogenesis system could enhance the successful of the modern papaya breeding program through genetic transformation.